2016
DOI: 10.1590/0104-6632.20160333s20150136
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aerobic and Anaerobic Biodegradability and Toxicity Assessment of Real Pharmaceutical Wastewater From Industrial Production of Antibiotics

Abstract: -This study evaluates aerobic and anaerobic biodegradability and toxicity of a real pharmaceutical wastewater, which focuses on antibiotics production. Zahn-Wellens and Organization for Economic Cooperation and Development (OECD) methodologies were applied in order to verify the wastewater's biodegradability and Microtox® analysis was performed for toxicity tests. Tests achieved more than 89% and 63% of Total Organic Carbon reduction, showing 80% and 50% of antibiotic removal, for aerobic and anaerobic process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 23 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…This is corroborated by the reduction of volatile suspended solids. The latter is consistent with the studies carried out by Marcelino et al, (20) and Becerra (7) , in which they found that the test substances present in wastewater are absorbed in the aerobic sludge, rather than mineralized. Research carried out in Europe by Greenpeace (21) , has shown that the volatilization phenomena presented by aerobic biological treatments affect, both directly and indirectly, the quality of natural resources and biodiversity.…”
Section: Biodegradability Testsupporting
confidence: 93%
“…This is corroborated by the reduction of volatile suspended solids. The latter is consistent with the studies carried out by Marcelino et al, (20) and Becerra (7) , in which they found that the test substances present in wastewater are absorbed in the aerobic sludge, rather than mineralized. Research carried out in Europe by Greenpeace (21) , has shown that the volatilization phenomena presented by aerobic biological treatments affect, both directly and indirectly, the quality of natural resources and biodiversity.…”
Section: Biodegradability Testsupporting
confidence: 93%
“…Nowadays, the production and consumption of antibiotics and antimicrobial agents have increased dramatically in China, leading to serious antibiotic contamination problems [1][2][3]. Sulfamethazine (SMZ) is a sulfonamide antibiotic containing aromatic amines and sulfonamide functional groups, which is frequently detected in the environment [4,5]. Due to the potential harm it could do to both the biological environment and human health, it is therefore imperative to develop stable and efficient removal technologies before the discharge.…”
Section: Introductionmentioning
confidence: 99%
“…The other commonly used antibiotic is Ampicillin, which is classified as a β-lactam antibiotic and can destroy gram-negative and gram-positive bacteria [5]. However, these antibiotics are not completely biodegradable [6][7][8][9], with the consequence that the residues that remain may induce the development of antibiotic-resistant microorganisms even if the presence of these compounds in the aquatic environment is in low concentration [10].…”
Section: Introductionmentioning
confidence: 99%